Disnarration in Kazuo Ishiguro’s The Remains of the Day - Sareh Khosravi (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2022)
ABSTRACT This study discusses the disnarrated in Kazuo Ishiguro’s The Remains of the Day by focusing on Gerald Prince’s ideas on the disnarrated. According to Prince, disnarration refers to events that have not happened but have been mentioned in the narrative. There are two modes for representing disnarration in the narrative of the novel: implicit and explicit. In the former, the disnarrated is represented by techniques like symbols, metonymies and foil characters. In the later, it is explicitly stated that a particular event could have happened but have not happened. However, based on Ishiguro’s preoccupation with the suppression of meaning, the majority of disnarrated narratives are implicit rather than explicit. The narrator’s implicit remarks signify his lost opportunities for the things he could have. Nearly at the ending of the novel, however, the narrator offers a more honest attitude to the readers by explicitly talking about his regrets and lost opportunities.